Assessment of The Basketball Skills for Secondary School Students in Henan Province, China - Zhang, Xianfeng; Rittisom, Suvachai; Hongaeanyatham, Prakit (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: Henan Province is currently prioritizing sports, particularly basketball, offering numerous opportunities for youth to excel. Researchers are focusing on the evolution of basketball education in junior high schools across Henan Province, recognizing the sport's significance within the curriculum and its potential for student development. Materials and Methods: The research study utilized a sample mean group consisting of students at the secondary school level 2 in 10 schools within Henan Province. The sample size of 302 students was determined using Krejcie and Morgan's ready-made sample table. This sample included 157 male students and 145 female students, selected through multi-stage random sampling. Test tool that Drib test, Harrison, Field Goal speed test of Johson and Wall Baunce test of Bunn statistic used parentage valve, Average ( ) Derivation (SD) and T score Results: The assessment of basketball skills among male students in Secondary 2 in Henan Province for the 2023 academic year showed high proficiency. For dribbling in a zigzag, the mean was 25.99 with an SD of 1.63; for shooting a goal quickly, it was 15.10 with an SD of 1.79; and for receiving the ball against the wall, it was 13.39 with an SD of 1.58. For female students, a mean below 17.3 is considered a very high level (T score of 35), while a mean above 24.63 is considered a very low level (T score of 55 or more). Conclusion: Advocates for athletes to prioritize physical training, mental preparation, and skill practice, highlighting the interconnectedness of body condition and mental state in athletic success.